решите уравнения:

-7х+5 ( 2х- 3 ) = 6

5х - 7(3-х)=2х+11

2(х+5)-3(х-2)=10

2(5-х)-5(2х-3)=1

(х-2)(х-3)=х(х+1)

(х+4)(х+6)-х^2=30

2

Ответы и объяснения

2013-03-12T17:47:34+04:00

-7х+5(2х-3)=6

-7х+10-15=6

-7х+10х=6+15

3х=21

х=21

х=21/3

х=7

 

Лучший Ответ!
2013-03-12T17:52:52+04:00

№1.-7х+5 ( 2х- 3 ) = 6

-7х+10х-15=6

-7х+10х=6+15

3х=21

х=21:3

х=7

№2. 5х - 7(3-х)=2х+11

-21+7х=2х+11

+7х-2х=11+21

10х=32

х=32:10

х=3,2

№3. 2(х+5)-3(х-2)=10

2х+10-3х+6=10

2х-3х=10-10-6

-х=-6

х=6

№4. 2(5-х)-5(2х-3)=1

10-2х-10х+15=1

-2х-10х=1-10-15

-12х=-24

12х=24

х=24:12

х=2

№5. (х-2)(х-3)=х(х+1)

х^2-3х-2х+6=х^2+х

х^2-3х-2х-х^2-х=-6

-3х-2х-х=-6

-6х=-6

6х=6

х6:6

х=1

№6. (х+4)(х+6)-х^2=30

х^2+6х+4х+24-х^2=30

6х+4х=30-24

10х=6

х=6:10

х=0,6